A catechol-O-methyltransferase genetic variant impacts functional movement in tactical athletes - Marcus K. Taylor; Lisa M. Hernández; Richard C. Allsopp; John J. Fraser (PLoS ONE, 2025)
Functional movement is a valuable indicator of physical performance, injury risk, and/or musculoskeletal impairment following injury. However, genetic variation and gene–environment interactions that may affect functional movement are largely unexplored. We recently reported a linkage between trauma exposure and functional movement in male tactical athletes. Here, we examined the effect of a common genetic variant, rs737865, within the catechol-O-methyltransferase gene on functional movement in specialized military personnel (N = 134). We also explored whether rs737865 modulated the influence of trauma exposure. Genotyping was determined from saliva, trauma exposure was self-reported using the Brief Trauma Questionnaire, and functional movement was evaluated using the Functional Movement Screen™. The effect of rs737865 on functional movement was evaluated using general linear models, while associations between trauma and functional movement were determined with regression models. An alpha level of 0.05 was set as the threshold for significance. In the standard three-genotype model (GG, AG, AA), rs737865 predicted functional movement (p = 0.03, η2p = 0.05). Specifically, GG (n = 9) exhibited the highest functional movement scores (mean [M] ± standard deviation [SD] = 17.2±1.9), followed by AG (n = 45; M±SD = 15.9±2.5), and then AA (n = 80; M±SD = 15.2±2.3). The connection between rs737865 and functional movement was preserved in both the dominant G model (G vs AA; p = 0.03, η2p = 0.04) and the dominant A model (A vs GG; p = 0.03, η2p = 0.03). The rs737865 variant also modulated the influence of trauma on functional movement. To our knowledge, this is the first discovery linking rs737865 to functional movement, which may lead to greater precision in musculoskeletal injury risk stratification and increased efficacy of strength and conditioning programs in tactical athletes. In resource constrained settings, genomic modeling may help to direct limited assets to at-risk subgroups (for screening purposes). It may also help to individualize, and enhance, strength and conditioning programs based on the genomic signature of a person’s training response.